Comparison Methods for Converting a Spindle Plant to Discrete System - M. Khairudin (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This study presents comparison methods in the conversion of a spindle plant in order to obtain an accurate discrete system when compared to a continuous system of spindle.  The accurate conversion results of the continuous system into discrete form are required for implementing the control system of spindle. Comparison methods that will be conducted to convert  the  continuous system of spindle plant into discrete system through zero-order hold (ZOH), first-order hold (FOH), impulse invariant dicretisation, tustin (bilinear), and pole-zero matching methods. The performances of each method in the conversion process have been presented. Conversion performances of continous spindle plant into discrete form using FOH method, showed more accurate compared to other methods. Performances of the conversion accuracy of FOH method have been evaluated in terms of transient responses analysis that closed similar results with a continuous system of spindle plant. At the closed similar transient responses for the discrete system using FOH method show the final value, time to peak, percertages overshoot and setlling time are 0.863 v, 0.910 s, 0 % and 0.550 s respectively.